Prostor v romanu Marjana Tomšiča Óštrigéca - Tucovič Sturman, Vladka (Jezik in slovstvo, 2022)
The article uses the insights of the spatial turn and so-called spatial literary studies to answer questions regarding the Istrian setting in Marjan Tomšič’s Novel Óštrigéca, the micro-locations into which it is divided, how they are represented or what determines them, and how the literary space determines the regionality of this novel. The setting of Óštrigéca is parallel – real and imaginary – while the central literary micro-location is a road in the Istrian countryside. The real Istrian literary space is directly defined by the geographical names for the places, the hills and the river, and indirectly defined by so-called spatial fragments, which are not geographical names but other linguistic elements that complete the notion of the literary space: dialectal vocabulary, recognisable local names for creatures, and the introduction of typically local features and elements of nature. The imaginary space is defined, among other things, by mythological creatures, elements of traditional medicine and rare natural phenomena
Keywords: dogajalni prostor; Istra; Istria; literary space; prostor; prostorski obrat; regionality; regionalnost; Slovene literature; Slovene writers; slovenska književnost; slovenski pisatelji; space; spatial turn; Tomšič, Marjan